6(3x-3)(x-4)=0

Simple and best practice solution for 6(3x-3)(x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3x-3)(x-4)=0 equation:


Simplifying
6(3x + -3)(x + -4) = 0

Reorder the terms:
6(-3 + 3x)(x + -4) = 0

Reorder the terms:
6(-3 + 3x)(-4 + x) = 0

Multiply (-3 + 3x) * (-4 + x)
6(-3(-4 + x) + 3x * (-4 + x)) = 0
6((-4 * -3 + x * -3) + 3x * (-4 + x)) = 0
6((12 + -3x) + 3x * (-4 + x)) = 0
6(12 + -3x + (-4 * 3x + x * 3x)) = 0
6(12 + -3x + (-12x + 3x2)) = 0

Combine like terms: -3x + -12x = -15x
6(12 + -15x + 3x2) = 0
(12 * 6 + -15x * 6 + 3x2 * 6) = 0
(72 + -90x + 18x2) = 0

Solving
72 + -90x + 18x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '18'.
18(4 + -5x + x2) = 0

Factor a trinomial.
18((1 + -1x)(4 + -1x)) = 0

Ignore the factor 18.

Subproblem 1

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {1, 4}

See similar equations:

| 43-y=174 | | 6g+27=36 | | y+63=8y | | (x-7)(-1)=0 | | .08=.03+.60*.05 | | 10y=21+7y | | .08=.03+.03 | | 3x+5=2(2x-1)1-(x-3) | | -3/5c-7=6 | | 227=142-u | | 18m+9=3(4m-9) | | (x-7)(4)=0 | | 23-x=275 | | -0.6c-7=6 | | 3-5x-7x=87 | | 14x-3=9x+5 | | 168=19-v | | 2+e=-2 | | ln(5x)+ln(10x)= | | 3(5x+3)=-5(5x-2) | | v+60=5v | | 3x+90=126 | | 6x=9y-6 | | 0.6(b-4)=-9 | | 8x-2y=41 | | 1.82= | | x(x+12)=(x-4)(x-4) | | ln(5x)+ln(10x)=4 | | 4-v=265 | | 6x+9y=65 | | Y-4+7y=24 | | -16=-4+4y |

Equations solver categories